HUBUNGAN PAPARAN KADAR TOLUENE DI UDARA DENGAN FUNGSI GINJAL PADA PEKERJA BAGIAN PENGECATAN PERUSAHAAN KAROSERI X MAGELANG - Ridwan Dwi Setiawan Habibie; Ari Suwondo; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2015)
Toluene was one of organic component solvents in the paint composition which served to dilute the paint. Toluene had volatility in room temperature, therefore toluene was the most dominant absorbed by the body through inhalation, the rest will absorbed by ingestion and skin in the process of spray painting in Karoseri Industry. Toluene had impacts on the health, one of them was impaired renal function. The aim of this study was to determine the association toluene exposure on the air with renal function in X Karoseri Industry painting workers Magelang. This study was quantitative with cros sectional approach. Sample used in this study were total sampling 26 workers. This study was analyzed using univariate and bivariate  with person product moment and rank spearman. The result showed that there was no association between work period with glomerulus filtration rate (GFR), ureum, and kreatinin level. There was no association between toluene concentration with glomerulus filtration rate (GFR) and ureum level. There was a association between creatinin level with toluene concentration. In painting workers research suggest to give purifying respiratory masks for painting workers to reduce the absorbtion into body.